1993
DOI: 10.1063/1.465785
|View full text |Cite
|
Sign up to set email alerts
|

Soluble conjugated polymers with degenerate ground state derivatives of poly(1,6-heptadiyne)

Abstract: We report the results of initial measurements on two derivatives of poly(1,6-heptadiyne): a di-ketone (PHDK) and a di-ester (PHDE). Both polymers have the degenerate ground state of poly(1,6-heptadiyne); both are soluble in common organic solvents. Electron spin resonance (ESR) measurements on pristine samples place an upper limit of 10−4 spins per monomer for both polymers. At low doping levels, we observe a single doping-induced absorption band at an energy of approximately half the π−π* gap, Eg/2; the dopin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In the case of poly͑1,6-heptadiyne͒, the doping is simulated by withdrawal of electrons from the molecules, following the experimental studies of p-doped derivatives reported by Pakbaz et al 9 are considered by using different numbers of monomer units within a doubly charged polymer unit cell. In the case of PDPHA, a study of the n doping is performed, first by simply adding electrons to the system, and second by adding both protons and electrons which then allows us to investigate the n-self-doping process in PDPHMA.…”
Section: Theoretical Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of poly͑1,6-heptadiyne͒, the doping is simulated by withdrawal of electrons from the molecules, following the experimental studies of p-doped derivatives reported by Pakbaz et al 9 are considered by using different numbers of monomer units within a doubly charged polymer unit cell. In the case of PDPHA, a study of the n doping is performed, first by simply adding electrons to the system, and second by adding both protons and electrons which then allows us to investigate the n-self-doping process in PDPHMA.…”
Section: Theoretical Methodologymentioning
confidence: 99%
“…Since the onset for the first optical transition in poly͑di-ethyldipropargylmalonate͒ and poly͑3,3-dipropargyl-2,4-octanedione͒ is measured to be about 1.9 eV ͑with a peak at about 2.3 eV͒, 9 the comparison with VEH-calculated bandgaps indicates that the systems are actually more planar in the solid state than the ϭϪ69°or ϭ47°structures optimized on isolated chains. At the VEH level, the bandgap becomes on the order of 1.9 eV for ϷϮ10°.…”
Section: Electronic Structurementioning
confidence: 95%
See 2 more Smart Citations
“…Measurement of the diffraction efficiency at zero time delay (q) yielded q = lop4. Because the pulsed laser operated at 620 nm, we were pumping into the leading edge of the r-IT* absorption band (10). Consequently, we expected the laser-induced gratings to have contributions from changes in the absorption coefficient (Act) and from changes in the index of refraction (An); the former leads to an amplitude grating and the latter to a phase grating.…”
mentioning
confidence: 99%